Measurement of thermoelectric potential coupling coefficient for sandstone rock sample - Jaafar, Mohd. Zaidi (2015)
Excessive water production is one of the main problems that occur during hydrocarbon production. During water injection, the less viscous water which has higher mobility than the reservoir fluid, tends to by-pass the oil. This phenomenon is normally called water fingering. Density difference between denser water and oil makes the water segregate to the bottom of layer, creating water tongue. Uncontrolled excessive water production will reduce oil production potential and increase the cost for water management and treatment. This phenomenon is economical unfavorable. Intelligent well integrated with monitoring systems and inflow control valve (ICV) has been applied in producing hydrocarbon. The excessive flow of water into well can be controlled using ICV. There are various methods and approaches been proposed to control water production. One of them is by measuring the spontaneous potential (SP) using permanent sensor outside the insulated casing. However, thermoelectric (TE) potential could also contribute to the measurement of the SP. The main objective of this experiment is to measure TE potential across sandstone rock sample at four different salinities which are 0.001M, 0.01M, 0.1M, and 1.0M of brine (NaCl). The core samples dimension is 7.62 cm in length and 3.81 cm in diameter. Temperature difference up to 80°C was applied to rock sample inducing different TE potentials at different salinities. Gradual heating technique was applied in creating temperature difference by using a temperature controller. Three different experiments were conducted for each salinity and real-time voltage (V) and temperature (T) were recorded using data acquisition system. Then the TE coupling coefficient can be determined by calculating the slope after plotting Voltage versus Temperature Difference. The result is as the salinity increases, TE coupling coefficient decrease and drop to zero around 0.1M. The result shows small but still measurable thermoelectric coupling coefficients.